Analysis of Inventory Turnover in Improving Profitability at PT Artindo Pratama Sejahtera - Pertiwi Hari Sandi, Santi; Marshanda Putri, Rihana; Rosmawati , Ery (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze inventory turnover, profitability measured through the gross profit margin, comparisons with industry standards, and the role of inventory turnover in increasing profitability at PT Artindo Pratama Sejahtera during the 2020–2024 period. The study evaluates the relationship between inventory turnover and profitability, as well as compares the company’s performance with industry standards. The company’s financial statements are used as secondary data in this quantitative descriptive research. The analysis is conducted through the calculation of inventory turnover and gross profit margin ratios, which are then compared with industry standards to assess the company’s performance. The results of the study show that the company’s inventory turnover fluctuates and is mostly below industry standards, except in 2023 when the inventory turnover exceeded the standard. Meanwhile, the company’s profitability shows stable performance and remains consistently above industry standards throughout the research period. The conclusion of this study indicates that inventory turnover plays a role in supporting increased profitability but is not the only determining factor. The contribution of this research is expected to serve as a reference for management evaluation in improving the efficiency of inventory management, as well as a reference for future research in the manufacturing industry sector.